2003
DOI: 10.1016/s0254-0584(03)00089-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, phase transformation and dielectric properties of sol–gel derived Bi2Ti2O7 ceramics

Abstract: Sol-gel derived Bi 2 Ti 2 O 7 ceramic powders have been prepared from methoxyethoxides of bismuth and titanium (molar ratio of Ti/Bi = 1.23 and water/alkoxides = 1.31). The Bi 2 Ti 2 O 7 phase was stable at a low temperature (700 • C), but it then transformed into mixed phases of Bi 4 Ti

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(33 citation statements)
references
References 11 publications
2
31
0
Order By: Relevance
“…3, an impurity phase was formed at 550 • C. The diffraction peaks can be assigned to Bi 2 Ti 2 O 7 structure as reported in the ICPDS File No. 32-0118 [17,18]. When the temperature rised to 700 • C, the diffraction peaks belonging to Bi 2 Ti 2 O 7 disappeared, only diffractions belonging to pure perovskite phase were observed, and there is no evidence of a second phase at 700 • C and above.…”
Section: Resultsmentioning
confidence: 97%
“…3, an impurity phase was formed at 550 • C. The diffraction peaks can be assigned to Bi 2 Ti 2 O 7 structure as reported in the ICPDS File No. 32-0118 [17,18]. When the temperature rised to 700 • C, the diffraction peaks belonging to Bi 2 Ti 2 O 7 disappeared, only diffractions belonging to pure perovskite phase were observed, and there is no evidence of a second phase at 700 • C and above.…”
Section: Resultsmentioning
confidence: 97%
“…It was found that the amorphous dried gel was transformed into cubic pyrochlore Bi 2 Ti 2 O 7 (JCPDS file NO. 32-0118) in the temperature region between 500 and 600 1C [11,12]. Further increasing temperature above 600 1C, the characteristic peaks of KBT crystals appeared and at 700 1C, only pure KBT phase (JCPDS file NO.…”
Section: Resultsmentioning
confidence: 99%
“…The d values of the peaks agree very well with those given in JCPDS data cards for Bi 4 Ti 3 O 12 . The phenomenon of transformation between pyrochlore phase and perovskite phase has been found in many reports [14,22,23], indicating that perovskite phase is a more thermodynamically favored phase than pyrochlore phase.…”
Section: Resultsmentioning
confidence: 79%